Twelve years a slave ebook - Northup, Solomon (eStar Books, 2013)
The thrilling story of a free colored man, kidnapped in Washington in 1841, sold into slavery, and after twelve years of bondage is reclaimed by state authority from a cotton plantation in Louisiana.